PENGEMBANGAN MEDIA PAPAN NILAI TEMPAT PADA MATERI NILAI TEMPAT KELAS II SEKOLAH DASAR - Shofia Nadhzifah Salsabila (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT Mathematics learning for elementary school students requires concrete learning experiences so that abstract concepts can be understood more easily, especially in place value material. However, the learning process in grade II at SD Negeri Penggaron Kidul Semarang is still dominated by the use of whiteboards, textbooks, projectors, and handphones, resulting in limited student involvement in manipulative learning activities. This study was conducted to develop the Place Value Board (PANIPAT) learning media and to examine its feasibility and practicality in elementary school mathematics learning. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data were collected through interviews, questionnaires, and documentation involving material experts, media experts, teachers, and second-grade elementary school students. The results showed that PANIPAT obtained a material expert validation score of 86% and a media expert validation score of 94%, both categorized as highly feasible. In addition, teacher responses reached 88% and student responses reached 96.4%, both categorized as very good. These findings indicate that PANIPAT is capable of helping students understand place value concepts through more engaging and interactive hands-on learning activities. Therefore, PANIPAT has the potential to serve as an alternative mathematics learning medium that supports concrete learning experiences for elementary school students. ABSTRAK Pembelajaran matematika pada siswa sekolah dasar memerlukan pengalaman belajar yang konkret agar konsep abstrak lebih mudah dipahami, terutama pada materi nilai tempat. Namun, proses pembelajaran di kelas II SD Negeri Penggaron Kidul Semarang masih didominasi penggunaan papan tulis, buku, proyektor, dan handphone sehingga keterlibatan siswa dalam aktivitas manipulatif belum optimal. Penelitian ini dilakukan untuk mengembangkan media Papan Nilai Tempat (PANIPAT) sekaligus mengkaji tingkat kelayakan dan kepraktisannya dalam pembelajaran matematika sekolah dasar. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Pengumpulan data dilakukan melalui wawancara, angket, dan dokumentasi dengan melibatkan ahli materi, ahli media, guru, dan siswa kelas II sekolah dasar. Hasil penelitian menunjukkan bahwa PANIPAT memperoleh persentase validasi ahli materi sebesar 86% dan validasi ahli media sebesar 94% dengan kategori sangat layak. Selain itu, respons guru mencapai 88% dan respons siswa sebesar 96,4% dengan kategori sangat baik. Temuan tersebut menunjukkan bahwa PANIPAT mampu membantu siswa memahami konsep nilai tempat melalui aktivitas belajar langsung yang lebih menarik dan interaktif. Dengan demikian, PANIPAT berpotensi menjadi alternatif media pembelajaran matematika yang relevan untuk mendukung pembelajaran konkret pada siswa sekolah dasar.